2004
DOI: 10.1111/j.1365-2036.2004.02268.x
|View full text |Cite
|
Sign up to set email alerts
|

Randomized placebo‐controlled trial assessing the effect of bifidobacteria‐fermented milk on active ulcerative colitis

Abstract: SUMMARYBackground: Probiotics are efficacious for treating and maintaining remission of ulcerative colitis. Aim: To conduct a randomized placebo-controlled trial of bifidobacteria-fermented milk supplementation as a dietary adjunct in treating active ulcerative colitis. Methods: Twenty patients with mild to moderate, active, ulcerative colitis randomly received 100 mL/day of bifidobacteria-fermented milk or placebo for 12 weeks with conventional treatment. Results: Clinical and endoscopic activity indices and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
221
1
9

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 336 publications
(249 citation statements)
references
References 36 publications
2
221
1
9
Order By: Relevance
“…The efficacy of bifidobacteria-fermented milk (BFM) in the treatment of ulcerative colitis has been reported elsewhere [7,8] . To determine the anti-inflammatory activity of probiotic Bifidobacterium strains in the BFM, we firstly investigated the effects of these strains on the production of anti-inflammatory cytokine IL-10 by PBMNC isolated from UC patients in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy of bifidobacteria-fermented milk (BFM) in the treatment of ulcerative colitis has been reported elsewhere [7,8] . To determine the anti-inflammatory activity of probiotic Bifidobacterium strains in the BFM, we firstly investigated the effects of these strains on the production of anti-inflammatory cytokine IL-10 by PBMNC isolated from UC patients in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…There is evidence that probiotic treatment is effective against UC [3][4][5][6] . We have previously shown that treatment with bifidobacteriafermented milk (BFM) containing live bifidobacteria is more effective than the usual treatment in inducing [7] and maintaining remission [8] of ulcerative colitis. An improvement in the composition of intestinal flora by BFM may prevent the overgrowth of potentially pathogenic bacteria such as Bacteroides vulgatus, but we hypothesized that probiotic strains of bifidobacteria in BFM may directly interfere with the host signaling events that drive the intestinal inflammatory response.…”
Section: Introductionmentioning
confidence: 99%
“…similarly, Kato et al (ref. 31 ) found increased levels of faecal butyrate, propionate, and scFa acid concentrations in patients with active Uc (mild to moderate), who received BFm together with conventional treatment. in this pilot study, patients supplemented with BFm showed a significantly lower clinical activity index than the placebo group.…”
Section: Discussionmentioning
confidence: 99%
“…[149] Following a systematic review of studies using VSL#3 TM , E.coli Nissle 1917 and Yakult TM , Mallon et al concluded that the addition of probiotics to conventional medical therapy had no effect in overall remission rate in mild to moderate UC. [150][151][152] Other randomized controlled trials have also shown conflicting results with some showing a higher rate of remission (with VSL#3 or a combination of a prebiotic and B.longum) [153][154][155] and others showing little or no benefit (with E.coli Nissle 1917). [156] There are no recommendations regarding the use of probiotics as maintenance therapy in UC.…”
Section: Probiotics In Ibdmentioning
confidence: 99%